Colorectal cancer screening knowledge, attitudes and behavioural intention among Indigenous Western Australians - Christou Aliki; Thompson Sandra C (BMC, 2012)
Abstract Background Indigenous Australians are significantly less likely to participate in colorectal cancer (CRC) screening compared to non-Indigenous people. This study aimed to identify important factors influencing the decision to undertake screening using Faecal Occult Blood Testing (FOBT) among Indigenous Australians. Very little evidence exists to guide interventions and programmatic approaches for facilitating screening uptake in this population in order to reduce the disparity in colorectal cancer outcomes. Methods Interviewer-administered surveys were carried out with a convenience sample (n = 93) of Indigenous Western Australians between November 2009-March 2010 to assess knowledge, awareness, attitudes and behavioural intent in regard to CRC and CRC screening. Results Awareness and knowledge of CRC and screening were low, although both were significantly associated with exposure to media advertising (p = 0.008; p < 0.0001). Nearly two-thirds (63%; 58/92) of respondents reported intending to participate in screening, while a greater proportion (84%; 77/92) said they would participate on a doctor's recommendation. Multivariate analysis with logistic regression demonstrated that independent predictors of screening intention were, greater perceived self-efficacy (OR = 19.8, 95% CI = 5.5-71.8), a history of cancer screening participation (OR = 6.8, 95% CI = 2.0-23.3) and being aged 45 years or more (OR = 4.5, 95% CI = 1.2-16.5). A higher CRC knowledge score (medium vs. low: OR = 9.9, 95% CI = 2.4-41.3; high vs. low: 13.6, 95% CI = 3.4-54.0) and being married or in a de-facto relationship (OR = 6.9, 95% CI = 2.1-22.5) were also identified as predictors of intention to screen with FOBT. Conclusions Improving CRC related knowledge and confidence to carry out the FOBT self-screening test through education and greater promotion of screening has the potential to enhance Indigenous participation in CRC screening. These findings should guide the development of interventions to encourage screening uptake and reduce bowel cancer related deaths among Indigenous Australians.